2012
DOI: 10.2355/isijinternational.52.850
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plate-out Oil Film on Lubrication Characteristics in Cold Rolling

Abstract: Oil-in-water (O/W) emulsions are widely used in tandem cold rolling mills as coolants in order to reduce frictional forces and prevent heat scratches. Although the lubricating properties of O/W emulsions are determined by various factors, two particularly important ones are the amount of plate-out oil on the strip surface and the dynamic concentration mechanics of the emulsion at the inlet of roll bite, which has been a subject of much interest since the 1970s.As many studies have focused only on a single phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Plate-out oil film formation on the vertical strip and the horizontal strip is reported by Fujita and Kimura, 14 and there is no difference between the vertical strip and the horizontal strip. Also, Fujita and Kimura 14 developed a new rolling simulator for evaluating the relationship between plate-out oil film and lubrication characteristics, and reported that the lubrication characteristics on cold rolling were transferred in the amount of plate-out oil film at about 500 mg/m 2 .
Figure 5.Schematic view of apparatus used in plate-out experiments.
…”
Section: Methodsmentioning
confidence: 68%
See 2 more Smart Citations
“…Plate-out oil film formation on the vertical strip and the horizontal strip is reported by Fujita and Kimura, 14 and there is no difference between the vertical strip and the horizontal strip. Also, Fujita and Kimura 14 developed a new rolling simulator for evaluating the relationship between plate-out oil film and lubrication characteristics, and reported that the lubrication characteristics on cold rolling were transferred in the amount of plate-out oil film at about 500 mg/m 2 .
Figure 5.Schematic view of apparatus used in plate-out experiments.
…”
Section: Methodsmentioning
confidence: 68%
“…Azushima and Inakagi 12 proposed an estimation model for the oil film thickness using a new starvation model which considers the plate-out film on the roll and strip surfaces, and Guillaument et al 13 analyzed plate-out oil film formation after emulsion supply on the strip surface using CFD. Moreover, Fujita and Kimura 14 and Laugier et al 15 reported the influence of the plate-out oil film at the entry section of rolling on lubrication characteristics.…”
Section: Since 1980smentioning
confidence: 99%
See 1 more Smart Citation
“…The tandem rolling of stainless steels attains a relatively high rolling reduction rate, but large amounts of heat caused by friction and plastic deformation are generated. The high temperature causes the film to become thinner, 8,9) which increases the probability of incurring heat-streak defects. 10) Also, any roughness of the roll surface can give rise to defects.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have conducted numerous studies for emulsion rolling lubrication technology. Kimura and Fujita [1][2][3] established an estimation model of plate-out oil film after experimentally investigating the influences of plate-out time, emulsion flow, emulsion concentration, and oil droplet size on plate-out oil film formation characteristics through laboratory tests; then, these authors developed a hybrid lubrication system by combining recirculation and direct application systems. Azushima 4,5) proposed a numerical estimation method for oil film thickness during cold rolling by combining conventional starvation and plate-out models.…”
Section: Introductionmentioning
confidence: 99%